2015
DOI: 10.1248/bpb.b15-00062
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic Signaling Is a Novel Mechanism of the Cellular Response to Ionizing Radiation

Abstract: Recent studies suggest the effect of radiation is observed not only in irradiated cells but also in adjacent non-irradiated cells (bystander effect), although the mechanism has not yet been fully revealed. This bystander effect may be caused by intercellular communication via a gap junction or by messengers released from irradiated cells, such as reactive oxygen species, nitric oxide, or cytokines. However, an unknown mechanism is also possible in the bystander effect. On the other hand, it is known that extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 59 publications
0
20
0
Order By: Relevance
“…Immune and apoptotic cells release ATP through connexin and pannexin hemichannels during inflammatory responses and uncontrolled release of intracellular ATP pools can also occur during cell necrosis (Eltzschig et al, 2006;Chekeni et al, 2010). Mounting evidence also suggests that connexin 43-mediated ATP release from γ-irradiated cells causes the radiation-induced bystander effect where adjacent, non-irradiated cells exhibit physiological responses mediated by P2 receptors Ohshima et al, 2012;Tsukimoto, 2015;Kojima et al, 2017). Interestingly, the ionotropic P2X7 receptor also has been shown to mediate ATP release (Suadicani et al, 2006;Ohshima et al, 2010), likely through its sustained activation that leads to membrane depolarization and pore formation (Dahlquist et al, 1974;Weisman et al, 1984;Buisman et al, 1988), and P2X7R blockade has been shown to attenuate ionizing radiation (IR)-induced ATP release from salivary acinar cells (Gilman et al, 2019).…”
Section: The Role Of P2 Receptors In Salivary Gland Inflammationmentioning
confidence: 99%
“…Immune and apoptotic cells release ATP through connexin and pannexin hemichannels during inflammatory responses and uncontrolled release of intracellular ATP pools can also occur during cell necrosis (Eltzschig et al, 2006;Chekeni et al, 2010). Mounting evidence also suggests that connexin 43-mediated ATP release from γ-irradiated cells causes the radiation-induced bystander effect where adjacent, non-irradiated cells exhibit physiological responses mediated by P2 receptors Ohshima et al, 2012;Tsukimoto, 2015;Kojima et al, 2017). Interestingly, the ionotropic P2X7 receptor also has been shown to mediate ATP release (Suadicani et al, 2006;Ohshima et al, 2010), likely through its sustained activation that leads to membrane depolarization and pore formation (Dahlquist et al, 1974;Weisman et al, 1984;Buisman et al, 1988), and P2X7R blockade has been shown to attenuate ionizing radiation (IR)-induced ATP release from salivary acinar cells (Gilman et al, 2019).…”
Section: The Role Of P2 Receptors In Salivary Gland Inflammationmentioning
confidence: 99%
“…Recently, the bystander effect has been reported as a novel mechanism of radiation-induced biological activity. 2) This effect is mediated by soluble factors released from cells in response to radiation, such as ROS, nitric oxide or cytokines. 2) We have also shown that irradiated cells release nucleotides, such as ATP, ADP, uridine 5′-triphosphate (UTP) or uridine 5′-diphosphate (UDP), 3,4) and that release of these nucleotides into the extracellular environment mediates cellular responses to ionizing irradiation via activation of P2 receptors.…”
mentioning
confidence: 99%
“…2) This effect is mediated by soluble factors released from cells in response to radiation, such as ROS, nitric oxide or cytokines. 2) We have also shown that irradiated cells release nucleotides, such as ATP, ADP, uridine 5′-triphosphate (UTP) or uridine 5′-diphosphate (UDP), 3,4) and that release of these nucleotides into the extracellular environment mediates cellular responses to ionizing irradiation via activation of P2 receptors. 3,5) Extracellular nucleotides (ATP, ADP, UTP, and UDP) are well known as intercellular signaling molecules.…”
mentioning
confidence: 99%
“…Involvement of P2Y11 Receptors in IL-6 Production in Response to γ-Irradiation It has been reported that ATP is released after γ-irradiation of cells, 39) and therefore we focused here on the P2 receptors. Expression of P2X3, 4, 5, 6, P2Y1, 4, 6, 11, 12, 14 was confirmed in HaCaT cells (Fig.…”
Section: γ-Irradiation-induced Il-6 Production In Hacat Cellsmentioning
confidence: 99%
“…However, further research is needed to confirm this. The pannexin hemichannel, connexin hemichannel, maxi anion channel, vesicular nucleotide transporter (VNUT) and other anion channel are usually involved in the ATP release pathway, but involvement of an anion channel or a hemichannel has been reported in radiation-induced ATP release, 39) and maxi-anion channel is involved in the case of HaCaT cells. 25) Therefore, ATP release from HaCaT cells may be involved in γ-irradiation-induced IL-6 production.…”
Section: -23)mentioning
confidence: 99%